Lipase-catalyzed resolution of 1,3-dioxolane derivatives: synthesis of a homochiral intermediate for antifungal agents - Kim, YH; Cheong, CS; Lee, SH; Jun, SJ; Kim, KS; Cho, HS (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
Dioxolane alcohol (+/-)-1 and the corresponding acid (+/-)-2 were kinetically resolved into their respective enantiomers by lipase-catalyzed hydrolysis and esterification reactions. Various alcohols were tested to resolve the acid (+/-)-2, and the desired (2R,4R)-isomer of the acid was obtained with >96% ee as the best result. Halogenated solvents such as methylene chloride and 1,2-dichloroethane were found to raise the reactivity and selectivity of the system. After recrystallization, the purity of the desired (2R,4R)-acid could be increased to over 98% ee. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: KETOCONAZOLE; ESTER